2022
DOI: 10.3390/rs14071649
|View full text |Cite
|
Sign up to set email alerts
|

An Accuracy Assessment of Snow Depth Measurements in Agro-Forested Environments by UAV Lidar

Abstract: This study assesses the performance of UAV lidar system in measuring high-resolution snow depths in agro-forested landscapes in southern Québec, Canada. We used manmade, mobile ground control points in summer and winter surveys to assess the absolute vertical accuracy of the point cloud. Relative accuracy was determined by a repeat flight over one survey block. Estimated absolute and relative errors were within the expected accuracy of the lidar (~5 and ~7 cm, respectively). The validation of lidar-derived sno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Limitations arising from the terrain being surveyed must also be accounted for in mission planning. For example, reducing the number of laser returns that are acquired from high incidence angles will lead to more consistent point density in the final clouds (Deems et al, 2013;Dharmadasa et al, 2022), as demonstrated here when reconstructing the lower reaches of the deepest crevasses. Consistent point spacing across the scene is also required for deriving final surface models, as well as undertaking geometric analysis (Dharmadasa et al, 2022), with reductions in point density reducing confidence in results or even removing regions from the analysis entirely.…”
Section: Current Limitations Of Uav-ls For Glacial Applicationsmentioning
confidence: 86%
See 4 more Smart Citations
“…Limitations arising from the terrain being surveyed must also be accounted for in mission planning. For example, reducing the number of laser returns that are acquired from high incidence angles will lead to more consistent point density in the final clouds (Deems et al, 2013;Dharmadasa et al, 2022), as demonstrated here when reconstructing the lower reaches of the deepest crevasses. Consistent point spacing across the scene is also required for deriving final surface models, as well as undertaking geometric analysis (Dharmadasa et al, 2022), with reductions in point density reducing confidence in results or even removing regions from the analysis entirely.…”
Section: Current Limitations Of Uav-ls For Glacial Applicationsmentioning
confidence: 86%
“…For example, reducing the number of laser returns that are acquired from high incidence angles will lead to more consistent point density in the final clouds (Deems et al, 2013;Dharmadasa et al, 2022), as demonstrated here when reconstructing the lower reaches of the deepest crevasses. Consistent point spacing across the scene is also required for deriving final surface models, as well as undertaking geometric analysis (Dharmadasa et al, 2022), with reductions in point density reducing confidence in results or even removing regions from the analysis entirely. This was observed here in the frontal position change analysis where both the sub-daily and daily comparisons had regions of the glacier front removed due to insufficient point densities.…”
Section: Current Limitations Of Uav-ls For Glacial Applicationsmentioning
confidence: 86%
See 3 more Smart Citations